Enhancement of the action of alkylating agents by single high, or chronic low doses of misonidazole. - McNally, N. J. (Nature Publishing Group, 1983)
Misonidazole (MISO) given as a large single dose enhanced the action of cyclophosphamide (Cy) and melphalan (L-PAM) in two mouse tumours. Below a dose of about 500 mg kg-1 it had no chemosensitizing effect. When MISO was given as a series of small doses by repeat injection over an 8 h period, in order to stimulate human pharmacokinetics, it significantly enhanced the action of Cy in the SA F tumour. It also enhanced the action of Cy and L-PAM in the WHFIB tumour as assayed by tumour cell survival in vitro following treatment in vivo but not when the assay was tumour growth delay. There was no enhancement by MISO of the leukopenia due to Cy or L-PAM. The results suggest that, in some tumours there may be benefit from the combination of clinically relevant MISO doses with alkylating agents. The leucopenia induced by these agents should not be enhanced by the MISO.